Bad grandpa [videorecording (DVD)] - Tremaine, Jeff; Knoxville, Johnny, 1971-; Knoxville, Johnny, 1971-; Nicoll, Jackson
Johnny Knoxville reprises his Jackass role as 86-year-old Irving Zisman. Zisman is on a journey across America with the most unlikely companion: his eight-year-old grandson Billy. The duo will encounter male strippers, disgruntled child beauty pageant contestants, funeral home mourners, biker bar patrons, and a whole lot of unsuspecting citizens. Real people in unreal situations, making for one really messed up comedy.